Fortifikasi Tepung Rumput Laut (Eucheuma cottonii) dan Tepung Ikan Umela (Lutjanus vitta) terhadap Karakteristik Fisik dan Kimia Kulit Pie - Rachel Shavia Eldin (Marinade, 2025)
Red Seaweed (Eucheuma cottonii) and Umela Fish (Lutjanus vitta) are two sources that are widely found in Bintan Island with nutritional content that is beneficial to the body. These sources are processed into flour which is used in making pie skin. This research aims to provide information about the diversification of pie skin using alternative food ingredients that are more balanced. The research method used a completely randomized design (CRD) with 4 treatments (F0, F1, F2, F3) which added seaweed flour (Eucheuma cottonii) (0%, 3%, 6%, and 9%) and umela fish flour (Lutjanus vitta) (0%, 6%, 9%, and 12%) with 3 repetitions. This research went through 3 stages, production of umela fish flour, pie skin making process with the addition of fish flour and seaweed flour and finally physical analysis, hedonic test to determine the level of consumer liking, as well as proximate chemical analysis and food fiber to determine the nutritional content. The results found that formula F2 with the addition of 6% of seaweed flour and 9% umela fish flour is the optimal combination that can meet the daily fiber needs of adults. The food fiber content in the pie skin of 12,13% and protein of 15,41% has met the SNI standard, however, the water and ash content exceeds the SNI standard, while the carbohydrate content does not reach the specified standard.